NUEVO REGISTRO DE CONEPATUS SEMISTRIATUS BODDAERT, 1784 (CARNIVORA: MUSTELIDAE) EN OAXACA, MÉXICO - Lira Torres, Iván; Sánchez- Cordero, Víctor (Instituto de Ecología, A.C., 2006)
Oaxaca is one of the most biodiverse regions in México harboring a high number of mammals species. In spite of the large number of mammal inventories conducted in this State, there are still many unexplored areas. We collected a specimen of the skunk Conepatus semistriatus outside of its known distribution range, located at La Fortaleza, Municipio de Santa Maria, Chimalapa. This new record pinpoints the need for continuing conducting biological inventories in regions holding a high biodiversity.